Pengembangan Media Pembelajaran untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Pelajaran Instalasi Penerangan Listrik - Azkiyah, Nisa; Hendri, Hendri (Jurnal Pendidikan Teknik Elektro, 2024)
This research is motivated by the lack of variety of learning media used in the learning process, the availability of books as a learning medium as well as the reason for the limitations of students in learning Electrical Lighting Installation material. This study uses a pure experimental research method. This study uses two classes consisting of an experimental class and a control class. For the experimental class, treatment was given using Android-based i-spring suite learning media, and the control class was not given treatment. The subjects in the study are class XI TITL 1 as an experimental class and XI TITL 2 as a control class where the number of students in each class is 23 people. The technique used for data collection in the study used test instruments and questionnaires for students' learning motivation towards the i-spring suite android based learning media. The results of the validation test of the learning media provided by the validator received a very valid category. The results of the learning motivation questionnaire of students who used the t-test showed the influence of i-spring suite learning media on learning motivation. With the results of the research data, it can be said that the development of android-based i-spring suite learning media can increase the motivation and learning outcomes of learning students in the Electrical Lighting Installation lesson at SMK N 1 Rao Selatan.